A Multidimensional Approach to Social Support: The Questionnaire on the Frequency of and Satisfaction with Social Support (QFSSS) - García-Martín, Miguel Ángel; Hombrados-Mendieta, Isabel; Gómez-Jacinto, Luís (Universidad de Murcia, 2016)
The Questionnaire on the Frequency of and Satisfaction with Social Support (QFSSS) was designed to assess the frequency of and the degree of satisfaction with perceived social support received from differ ent sources in relation to three types of support: emotional, informational, and instrumental. This study tested the reliability of the questionnaire scores and its criterion and structural validity. The data were drawn from survey interviews of 2042 Spanish people. The results show high internal consistency (values of Cronbach’s alpha ranged from .763 to .952). The correlational analysis showed significant positive associations between QFSSS scores and measures of subjective well-being and perceived social support, as well as significant negative associations with measures of lone liness (values of Pearson’s r correlation ranged from .11 to .97). Confirma tory factor analysis using structural equation modelling verified an internal 4-factor structure that corresponds to the sources of support analysed: partner, family, friends, and community (values ranged from .93 to .95 for the Goodness of Fit Index (GFI); from .95 to .98 for the Comparative Fit Index (CFI); and from .10 to .07 for the Root Mean Square Error of Ap proximation (RMSEA)). These results confirm the validity of the QFSSS as a versatile tool which is suitable for the multidimensional assessment of social support.
Keywords: Relaciones humanas; SEM; Perceived social support; Interpersonal relationships; Multidimensional assessment; Confirmatory factor analysis; Psychometric properties